Eksplorasi Reka Struktur Pada Pemanfaatan Limbah Kain Twill Gabardine - Liandra Khansa Utami Putri; Dian Widiawati (JURNAL RUPA, 2020)
Starting from the phenomenon of increasing patchwork waste generated from garment factories or the so-called convection industry in DKI Jakarta, according to the Ministry of Industry (2020) in Indonesia there are 1,535 factories which are still actively producing and also have a variety of patchwork waste . During the production period, it will produce a large amount of solid waste due to high sales. According to the survey data one of the research sites is the convection industry / garment factory PT. Farah Textile, located in East Jakarta, where there is a waste waste in the factory which amounts to approximately ± 750 kilo grams per month, waste wastes produce various kinds of pieces. Not all types of waste can be sold. While factory workers are less than optimal in utilizing the remaining patchwork waste, so there is a lot of patchwork waste left over and cannot be treated. The data collection methodology in this study uses a qualitative approach and an experimental method. There will be several stages of research to be carried out, in order to complete the data for research. Qualitative approaches and experimental methods will be applied to this waste research study. From the design process to be achieved in order to be able to reprocess the waste patchwork variant, so that it becomes a material sheet that is made optimally, into a fashion product concept and also produces good economic value. In making a fashion product that is used as a business opportunity, to increase the economic value of a product made (up-cycled). Aim to maintain the environment and create a zero waste product. The results of this exploration study aim to be able to treat the waste waste that is quite a lot in the factory environment, with different sizes and has been classified according to needs. With the aim of creating a new sheet of fabric and can be applied to a fashion product.